The possibility of determining the systolic function of the left ventricle using a single-channel electrocardiogram monitor with photoplethysmography. (14th October 2021) - Sagirova, Z H N; Kuznetsova, N O; Gogiberidze, N A; Gognieva, D G; Chomakhidze, P S H; Kopylov, P H Y U
Abstract: Introduction: Assessment of the systolic function of the left ventricle is the basis for the timely diagnosis and treatment of various diseases of the cardiovascular system. Regular monitoring of the systolic function is very often necessary. Remote assessment of the left ventricular systolic function can provide more thorough and convenient monitoring of the patient's condition. Purpose: The determination of the left ventricular systolic function using a single-channel electrocardiogram (ECG) monitor with photoplethysmography function. Methods: The study prospectively included 400 patients aged 18 and over with various pathologies of the cardiovascular system. All study participants underwent echocardiography and the indicators of the left ventricular (LV) systolic function were determined: LV ejection fraction (LV EF), LV outflow tract velocity time integral (LVOT VTI). Recording of the electrocardiogram (I standard lead) and the photoplethysmogram (PPG) using a single-channel ECG monitor with photoplethysmography were performed in all patients. The single-channel electrocardiogram monitor is a portable electrocardiograph with photoplethysmography in the form of a smartphone case. The ECG and PPG parameters were calculated and compared with echocardiography. Models for assessing the LV systolic function were built based on the obtained ECG and PPG parameters using the random forest algorithm. Results: A total of 400 ECG records and 400 PPG records were obtained. Then the parameters ECG and PPG were selected for constructing the models. We obtained three models for the ejection fraction (less than 55%, less than 40%, less than 30%) and two models for the LVOT VTI. The quality of each model was assessed by sensitivity, specificity, area under the ROC curve (AUC). For the model with the ejection fraction less than 55%, the AUC was 91.3% (0.844–0.982), sensitivity – 86.4%, specificity – 91.4%. AUC was 95.5% (0.903–1.000), sensitivity 100%, specificity 87.2% for the model with the ejection fraction less than 40%. For the model with the ejection fraction less than 30% AUC: 96.2% (0.900–1.000), sensitivity 100%, specificity 92.9%. Models for the LVOT VTI: less than 13cm (AUC: 77.6% (0.561–0.992), sensitivity 80%, specificity 78.1%) and less than 16cm (AUC: 78.2% (0.657–0.907), sensitivity 76.5%, specificity 77.4%). Conclusions: The models obtained based on ECG and PPG parameters had sufficiently high accuracy. Thus, using the ECG and PPG, it is possible to assess the LV systolic function. Therefore, it will be possible to perform the remote monitoring of the systolic function of the left ventricle using portable the single-channel electrocardiogram monitor with photoplethysmography. FUNDunding Acknowledgement: Type of funding sources: None.